Support with Groups in Social Work: An Interfocal Model for the Understanding and Systematization on Praxis - Arija Gisbert, Belén (Cuadernos de Trabajo Social, 2012)
This article presents the point of view of the author on the help relationship, particularly on supporting groups in Social Works, It provides some current and rigorous experiences as well, that serve to encourage new initiatives for groups and community participation. It is an invitation to imagine and stage new scenes of constructive ownership. Further, congruent with the so-called intermodal perspective or theoretical framework, the author shares a proposal of group chronicling or a praxis systematization model. An alternative for reflection that can be adapted and tailored to different contexts where it is already being used with the intent to help the group understand and access background. As professional, we seek to thing togheter, cooperate and feel the group reflexively with the group itself. She defends the idea that the methodology being used must be based on participant action-research. She shopes that the theory will live as as a support and a guide and not as an unknown universe far from practice. The author seeks to build bridges between the academid and professionaol worlds, to draw, among other things, a new, hopeful perspective for professional and for the people with whom they work, in that Social Work with grups will have a central, necessary presence in these times of crisis and change.